Elites and Corruption: A Theory of Endogenous Reform and a Test Using British Data. (April 2015) - Popa, Mircea
Abstract : Eighteenth-century Britain displayed patterns of corruption similar to those of developing countries today. Reforms enacted in the late eighteenth and early nineteenth centuries eliminated many of these patterns. This article develops a theoretical argument that seeks to explain why the British elite enacted anticorruption reforms and provides evidence using a new data set of members of the House of Commons. The author argues that the shock that pushed the British elite from preferring the old corrupt regime to preferring the reformed one was an increase in government spending and a corresponding increase in the costs of tolerating corruption. Features unique to Britain allowed the reformist outcome to emerge and illuminate why such an outcome is difficult to achieve in general.